The Influence of Radio in Enhancing Farmers' Perceptual Situation in Problem Solving towards Insufficient Information Delivery - Ismail I.B.; Rosidayu Sabran; Mohd Yahya Mohamed Ariffin (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by WOS/SCOPUS